C=C Bond Oxidative Cleavage of BODIPY Photocages by Visible Light. Issue 44 (9th July 2021) - Xu, Youwei; Lin, Shanmeng; He, Rongkun; Zhang, Yichuan; Gao, Quan; Ng, Dennis K. P.; Geng, Jin
Abstract: Photocages for protection and the controlled release of bioactive compounds have been widely investigated. However, the vast majority of these photocages employ the cleavage of single bonds and high‐energy ultraviolet light. The construction of a photoactivation system that uses visible light to cleave unsaturated bonds still remains a challenge. Herein, we report a regioselective oxidative cleavage of C=C bonds from a boron‐dipyrrolemethene (BODIPY)‐based photocage by illumination at 630 nm, resulting in a free aldehyde and a thiol fluorescent probe. This strategy was demonstrated in live HeLa cells, and the generated α‐formyl‐BODIPY allowed real‐time monitoring of aldehyde release in the cells. In particular, it is shown that a mannose‐functionalized photocage can target HepG2 cells. Abstract : The regioselective oxidative cleavage of a C=C bond from a boron‐dipyrrolemethene (BODIPY) photocage has been realized under 630 nm illumination; this generated an aldehyde compound and a thiol fluorescent probe. This reaction was demonstrated inside live cells by monitoring the aldehyde release in real time. In particular, the photocage can easily be functionalized with a mannose group so as to acquire the ability to target cancer cells.